The Armor of a Researcher: A Critical, Material Engagement with Somatic Experiences - Janne Mascha Beuthel (Diseña, 2022)
Design researchers and practitioners continuously engage with humans in their work, which can translate into encountering personal stories, challenging questions, and facing expectations. The researcher can be torn between remaining ‘professional’, which is often connoted to being ‘neutral’, and engaging their own emotions, vulnerabilities, and insecurities. This paper presents a soma design process that was informed by the autobiographical experiences of the author. The result is a wearable artifact named ‘The Armor of a Researcher’. The artifact embodies somatic experiences of ‘doing research’ and ‘being a researcher’ during qualitative studies with participants. It is intended to be thought-provoking and points towards reflections on professionalism. Physical materials are assembled into a wearable form, which allows others to engage with them through their own bodies. Finally, themes that The Armor has evoked in others are described; these outline knowledge that the artifact puts forth to HCI.